"Pollical palmar interosseous muscle" (musculus adductor pollicis accessorius): Attachments, innervation, variations, phylogeny, and implications for human evolution and medicine. (29th October 2012) - Bello‐Hellegouarch, Gaelle; Aziz, M. Ashraf; Ferrero, Eva M.; Kern, Michael; Francis, Nadia; Diogo, Rui
Abstract Most atlases and textbooks dealing with human anatomy do not refer to the "pollical palmar interosseous" (PPI) muscle of Henle. In order to undertake a fresh and detailed study of this muscle and to thus better understand human comparative anatomy and evolution, we: 1) analyze the frequency of the PPI in a large sample of human hands; 2) describe the attachments, innervation and varieties of the PPI in these hands; 3) compare the data obtained with the information available in the literature; and 4) discuss the phylogenetic origin of the PPI and the implications of our observations and comparisons for medicine and for the understanding of human evolutionary history. Within the 72 hands dissected by us, the PPI is present in 67 hands (93%), commonly having a single muscular branch, originating from the medial side of the base of metacarpal I only, inserting onto the medial side of the base of the pollical proximal phalanx and/or surrounding structures (e.g., ulnar sesamoid bone, wing tendon of extensor apparatus), and passing at least partially, and usually mainly, medial to the princeps pollicis artery. A careful study of the human PPI, as well as a detailed comparison with other mammals, strongly suggest that the muscle is evolutionarily derived from the adductor pollicis, and namely from its oblique head. Therefore, we propose that PPI should be designated by the name musculus adductor pollicis accessorius, which indicates that the muscle is most likely a de novo structure derived from the adductor pollicis. J. Morphol., 2013. © 2012 Wiley Periodicals, Inc.